PELATIHAN PEMBUATAN KERIPIK DAN STIK KELAPA DALAM MENINGKATKAN JIWA WIRAUSAHA PADA IBU RUMAH TANGGA DI DESA TADOLOIYO TRANS KABUPATEN KONAWE UTARA - Leni Saleh; Syarbiah, Sarty (Fakultas Pertania Universitas Muara Bungo, 2023)
The aim of holding this PKM activity is to diversify coconut into chips and sticks for housewives in RT 002 Tadoloiyo Trans Village, Oheo District. The selected participants were 10 people who had coconut trees in their yard. The activity stages were counseling and practice. PKM activities were carried out well, participants were very enthusiastic in taking part in PKM activities. Monitoring results showed that the amount of increase in participants' knowledge and skills from 100% of the 10 participants answered that they did not know before the training activity in making chips and coconut sticks increased to 100% or 10 participants answered that they knew and were able after the training. This shows that training activities can be said to be successful because there is an increase in the knowledge and skills of the training participants.